Financialization of the commodity future markets: a SVAR model approach - Momoli, Tommaso (2017)
This is a study regarding the impact of the index investments in the Commodity Future Market. The models applied, focus on the Causal Analysis and the Impulse Response Function through an orthogonalisation of the Vector of Auto Regression (SVAR), this allow to extract lead/lag correlation between the Index and First nearby Return for different Futures Sectors and in addition response to shocks in different equation. The study is divided in three different period, to reflect before and after the Financialization and then after the introduction in the market of the new generation of commodity Indexes. The results show a different behaviors of the parameters throughout time with a particular emphasis for the most traded Commodities to lead the others.